2004
DOI: 10.5860/crl.65.5.400
|View full text |Cite
|
Sign up to set email alerts
|

Historians and Their Information Sources

Abstract: This article reports on a survey of historians and a citation analysis undertaken to revisit the questions treated in Margaret F. Stieg’s 1981 article published in College & Research Libraries. It examines which materials historians consider to be the most important and how they discover them. Their attitudes toward and use of electronic materials were also studied. Many characteristics of historians’ information needs and use have not changed in a generation: informal means of discovery like book reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 9 publications
7
91
0
2
Order By: Relevance
“…As the RePAH team have argued, most humanities users distrust pre-culled or pre-analysed collections, and prefer to make their own decisions about the data that they find, from extensive resource collections (Brown et al, 2007: p.22). A similar preference for recall over precision was noted in historians by Dalton and Charnigo (2004) archives. Instead they, and the web resources that they produce, may now be an aid to further resource discovery.…”
Section: Information Collectionsmentioning
confidence: 71%
See 2 more Smart Citations
“…As the RePAH team have argued, most humanities users distrust pre-culled or pre-analysed collections, and prefer to make their own decisions about the data that they find, from extensive resource collections (Brown et al, 2007: p.22). A similar preference for recall over precision was noted in historians by Dalton and Charnigo (2004) archives. Instead they, and the web resources that they produce, may now be an aid to further resource discovery.…”
Section: Information Collectionsmentioning
confidence: 71%
“…Bates' work and that of Dalton and Charnigo (2004) and Whitmire (2002) has also shown that those humanities scholars who use digital resources tend to be demanding of the quality of resources and are capable of constructing complex search strategies, given appropriate training.…”
Section: Humanities Information Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…The iconographic sources included paintings, illustrations, sculptures, ceramics and other objects. In terms of mediation, the sources were classified as primary when they provided direct information about the object of study without mediation (Dalton and Charnigo 2004), regardless of whether the original records or the transcripts were primary or secondary. The types of primary written sources were classified as official documents (e.g., issued by former government agencies, kingdoms), manuscripts (e.g., codices, written literature, religious books and diaries and writings of travellers, naturalists and historians) and letters (unofficial writing directed to others) and prescriptions (medical or cooking prescriptions).…”
Section: Methodsmentioning
confidence: 99%
“…This work has also further delineated the types of sources that scholars use for data and evidence-noting a strong distinction between primary sources and secondary sources [2,4,6,7,15,17]. Research in this vein has also explored topic selection [4] and how researchers search for and locate sources in physical and digital environments [1,2,3,6,7,8,9,14,15,17].…”
Section: Related Workmentioning
confidence: 99%